2018
DOI: 10.1002/ange.201810199
|View full text |Cite
|
Sign up to set email alerts
|

Plasma‐Triggered Synergy of Exfoliation, Phase Transformation, and Surface Engineering in Cobalt Diselenide for Enhanced Water Oxidation

Abstract: Various strategies,s uch as increasing active site numbers and structural and surface engineering, have been used to improve the oxygen evolution reaction (OER) performance of transition-metal dichalcogenides.H owever,i t is challenging to combine these strategies in one system to realizet he full catalytic potential. Now,a nA r/O 2 plasma method is used to simultaneously induce exfoliation, surface reorganization (formation of an oxidative layer with rich oxygen vacancies), and phase transformation (cubic-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…24 It is also noteworthy that the plasma technology with good controllability (e.g., Ar, O 2 , and/or N 2 plasma source type, power density, and processing time) is another promising approach to obtaining uniformly vacancy defects in carbon-or metal-compound-based nanomaterials. 25,26 Furthermore, the obtained defect structures in carbons, transition-metal oxides, and TMDs (e.g., MoS 2 and CoSe 2 ) can be further processed by non-metal-and metal-atom doping to form various dopant-defect coordination motifs to not only stabilize the topological structures of defects but also further manipulate the local electronic distribution through the diverse coordinated configurations. 27,28 Analogous to plasma technology, a high-pressure hydrogenation process has been recently reported to treat a 2D iron-cobalt oxide (Fe 1 Co 1 O x ) via controllable hydrogen pressure and annealing temperature with the purpose of tuning its oxygen vacancy density.…”
Section: Categories Of Defects and Preparation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…24 It is also noteworthy that the plasma technology with good controllability (e.g., Ar, O 2 , and/or N 2 plasma source type, power density, and processing time) is another promising approach to obtaining uniformly vacancy defects in carbon-or metal-compound-based nanomaterials. 25,26 Furthermore, the obtained defect structures in carbons, transition-metal oxides, and TMDs (e.g., MoS 2 and CoSe 2 ) can be further processed by non-metal-and metal-atom doping to form various dopant-defect coordination motifs to not only stabilize the topological structures of defects but also further manipulate the local electronic distribution through the diverse coordinated configurations. 27,28 Analogous to plasma technology, a high-pressure hydrogenation process has been recently reported to treat a 2D iron-cobalt oxide (Fe 1 Co 1 O x ) via controllable hydrogen pressure and annealing temperature with the purpose of tuning its oxygen vacancy density.…”
Section: Categories Of Defects and Preparation Strategiesmentioning
confidence: 99%
“…Since then, such a plasma-engraving strategy has also been employed in exfoliation of bulk 2D materials, such as CoSe 2 , to introduce defects and exposure more active sites. 26 Besides anion defects, cation defects have also been proved to promote OER properties. Shao and co-workers found that the A-site cation defect of a perovskite type (ABX 3 ) LaFeO 3 can greatly enhance both the OER and ORR activities because of 60 Copyright 2016 American Chemical Society.…”
Section: Oxygen Evolution Reactionmentioning
confidence: 99%
“…However, a high voltage is still needed to drive the reaction process because of the sluggish kinetics for OER, especially in acidic conditions 811 . Significant efforts have been undertaken to design novel catalysts to overcome this obstacle, including heteroatoms doping, functionalization, and so on 1216 . Although much progress in developing bifunctional electrocatalysts for alkaline water splitting has been realized, the overpotential and corrosion resistance are still far from satisfactory under harsh acidic conditions, which hamper the development of proton exchange membrane water electrolyzers 1719 .…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical water splitting, including hydrogen evolution reaction and oxygen evolution reaction (OER), provide an efficient and environmentally friendly way for large-scale hydrogen production with high purity. To date, alkaline water splitting technologies have been well established and are commercially available for industrial H 2 production (Jin et al, 2016;Suen et al, 2017;Zheng et al, 2016;Wang et al, 2018aWang et al, , 2018bZhuang et al, 2019;Zhou et al, 2019). Nevertheless, compared with alkaline water splitting, acidic water splitting using proton exchange membrane (PEM) electrolyzer offers great advantages such as higher ionic conductivity, fewer unfavorable reactions, high voltage efficiency, and faster system response (Nong et al, 2015;Sardar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%